The Constitution in the Digital Era: Is the 1945 Constitution Ready to Address Cyber Threats and Data Security? - Fitri Kartika Sari; Salman Salman; Febrian Chandra; Alya Lavina Arken (Verdict: Journal of Law Science, 2026)
Digital governance, electronic transactions, cloud infrastructure, and public-sector data processing have transformed constitutional law in Indonesia. Cyberattacks, ransomware, data breaches, unlawful surveillance, and insecure personal data processing are no longer merely technical problems; they challenge constitutional guarantees of privacy, legal certainty, personal security, public service continuity, and state sovereignty. This article examines whether the 1945 Constitution of the Republic of Indonesia is normatively prepared to respond to cyber threats and personal data security risks. It asks, first, how the Constitution guarantees the protection of privacy and personal data security, and second, to what extent the state is constitutionally obliged to protect cyber sovereignty and respond to digital security threats. This research uses normative legal research with statutory, conceptual, case, and limited comparative approaches. The legal materials include the 1945 Constitution, the Personal Data Protection Law, the Electronic Information and Transactions Law, cybersecurity regulations, Constitutional Court decisions, and relevant legal scholarship. The article finds that the 1945 Constitution provides an implicit but strong basis for personal data protection through Articles 28G (1), 28D (1), 28H (4), 28F, 28I (4), and 28J. However, constitutional readiness remains incomplete at the operational level because cybersecurity governance is fragmented, independent personal data supervision has not been fully consolidated, and Indonesia still lacks a comprehensive statutory framework on cyber resilience. The article concludes that Indonesia’s Constitution is normatively adaptable but requires stronger statutory translation, independent supervision, risk-based cybersecurity duties, and constitutional proportionality safeguards. The originality of this study lies in integrating privacy, personal data protection, cybersecurity, and cyber sovereignty into one constitutional analysis, while prior studies generally examine these fields separately.